Primary hyperoxaluria type 1 - two case reports - Ganhão,Inês (2020)
Background: Primary hyperoxaluria type 1 is a rare autosomal recessive inherited disease, caused by mutations in AGXT gene, with an estimated incidence of 1:100.000 live births per year in Europe. Over 50% present with end stage renal disease at diagnosis. Case reports: The first case is a 14-year-old boy, second child to consanguineous parents, with history of recurrent lithiasis and ureteral dilatation starting 5 years before. Urine/stone analysis revealed calcium oxalate monohydrate crystals and markedly elevated urine oxalate excretion. Genetic tests confirmed a mutation in AGXT gene, c.1151T>C, in homozygosity. Two years after, nephrocalcinosis was identified and glomerular filtration rate gradually declined. Oxalate deposition in solid organs was excluded and successful orthotopic liver transplantation was performed, with stabilization of glomerular filtration rate. The second case is a 16-year-old girl, with recurrent episodes of renal colic. At diagnosis, she had obstructive hydronephrosis, multiple kidney stones and an estimated glomerular filtration of 42.1mL/min/1.73m2. Metabolic study showed hypocitraturia and hyperoxaluria. With dietetic measures and irregular treatment, urine oxalate excretion remained high but renal function improved. Genetic tests confirmed the presence of two pathologic variants in AGXT gene: c.731T>C and c.1151T>C in compound heterozygous. Conclusions: Recurrent urolithiasis and nephrocalcinosis in children along with family history/consanguinity should raise the suspicion of Primary Hyperoxaluria type 1. Conservative treatment may increase renal survival. Effects of systemic oxalosis must be screened when glomerular filtration rate declines below 30-50mL/min/1.73m2, and sequential or combined liver and kidney transplantation should be considered.